Kształtowanie umiejętności wnioskowania sylogistycznego - Smolak, Maciej (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2015)
The article consists of two parts. In the first part the author presents the characteristics of syllogistic reasoning, in the second part describes a set of exercises that are useful in teaching and developing the skill of syllogistic reasoning. The exercises belong to the teaching tools called interactive teaching methods and are of varying level of difficulty.
Forming the Ability of Syllogistic Inference
Keywords: syllogistic reasoning; syllogistic modes and figures; premise; conclusion; formal error; material error; ad rem argument; ad personam argument